Community outreach along the U.S./Mexico border: Developing HIV health education strategies to engage rural populations - Kristen Hernandez; Holly Mata; Elias Provencio Vasquez; Jacob Martinez (Rural Nurse Organization; Binghamton University, 2014)
Although there have been ongoing efforts in the United States to reduce new infections and improve care in people already living with the human immunodeficiency virus (HIV) and other sexually transmitted diseases/infections, Hispanics continue to bear a disproportionate burden of HIV/STI's. Reducing sexual health disparities is a key aspect in achieving health equity, and requires prioritization of groups most at risk for HIV/STI infection and least likely to have regular access to preventive healthcare. A growing body of nursing research highlights the need for addressing HIV-related health disparities among Hispanics. Our research in the U.S. - Mexico border region contributes to our ability to respond to HIV-related health disparities in Hispanic populations in the border region and beyond. Nurses have much to contribute to community-based efforts to promote societal and structural changes to reduce HIV risk, and bring unique expertise, experience, and perspective to community mobilization efforts. The purpose of this article is to explore strategies in disseminating HIV health education information and research findings in rural areas along the U.S./Mexico border. We conducted a needs assessment of clinics serving rural areas to enhance our dissemination and outreach efforts and to inform the development of culturally and linguistically appropriate health education materials. Increased capacity to integrate screening, referral, and education into routine clinic visits may improve prevention education, screening, and treatment engagement for STI's and HIV. Translating local research findings into improved clinical practice and services can promote health equity among medically underserved people in our region.  Prioritizing rural practitioners - who are often generalists and meet many of the health care needs of their community - is a replicable dissemination approach for nurses and other health professionals committed to building health equity.  DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i1.302  Key words: HIV; Health Equity; Hispanic health; rural health